The Change In Status Of The Tax Court Based On The Constitutional Court Decision Number 26/Puu-Xxi/2023 - Widia, Gilang; Ismail, Tjip (UNIVERSITAS PAKUAN, 2023)
The Tax Court is a judicial institution where tax disputes are resolved based on Law Number 14 of 2002 concerning Tax Courts (Tax Court Law). There is a problem regarding the dualism of guidance in the Tax Court, namely by the Supreme Court and the Ministry of Finance as stipulated in Article 5 paragraph (2) of the Tax Court Law. Related to the dualism of guidance in the Tax Court, the petitioners submitted a judicial review through Case Number 26/PUU-XXI/2023 because it was considered contrary to the constitution and reduced judicial independence. The results of this research show that after the Constitutional Court Decision No. 26/PUU-XXI/2023, the authority to provide non-technical judicial guidance to the Tax Court was transferred from the Ministry of Finance to the Supreme Court no later than December 31st, 2026. In addition to the impact on the organization, the Constitutional Court Decision also impacts the position and procedural law. Steps are needed that must be prepared in a planned and thoughtful manner by the government after the Constitutional Court Decision Number 26/PUU-XXI/2023 so that the transition process can run well in accordance with the predetermined timeframe so that in the future, the Tax Court becomes part of the judicial power that upholds judicial independence and does not take sides with any power.